2018
DOI: 10.1038/s41385-018-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

C3a receptor antagonism as a novel therapeutic target for chronic rhinosinusitis

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory disease with an unknown etiology. Recent studies have implicated the complement system as a potential modulator of disease immunopathology. We preformed proteomic pathway enrichment analysis of differentially increased proteins, and found an enrichment of complement cascade pathways in the nasal mucus of individuals with CRSwNP as compared to control subjects. Sinonasal mucus levels of C3 correlated with worse subjective disease severity, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…The upregulated burden of complement components in nasal polyps raised the question of which cells are involved in the complement protein syntheses. Complement production has been described for several epithelial cells [19,33] to be higher in nasal polyps [19]. We could demonstrate immunohistochemical C3 deposition at the epithelium and in the lumen in nasal polyps, but also for the inferior turbinate.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The upregulated burden of complement components in nasal polyps raised the question of which cells are involved in the complement protein syntheses. Complement production has been described for several epithelial cells [19,33] to be higher in nasal polyps [19]. We could demonstrate immunohistochemical C3 deposition at the epithelium and in the lumen in nasal polyps, but also for the inferior turbinate.…”
Section: Discussionsupporting
confidence: 52%
“…Drouin et al demonstrated the importance of C3a-C3aR interaction for asthma and its Th2 response, whereas C3aR deficiency leads to a decrease in eosinophils and diminished Th2related cytokines [32]. Also, Mulligan et al published observations showing reduced inflammation during C3aR inhibition in an Aspergillus fumigatus-induced CRS mouse model [19], supporting the detected results and the importance of C3a-C3aR interaction in humans. Nevertheless, although we could not show a prominent role for C5a and associated C5aR-bearing cells in NP, others postulate a role for increased MAC-formation along the epithelium and blood vessels leading to damage and loss of function [22,23].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, repeated intranasal inoculation of immunocompetent mice with A. fumigatus conidia exposing high levels of chitin skewed T-helper cells toward a type-2 allergic response [79]. Furthermore, genetic deficiency or functional inhibition of C3aR reduced inflammation and development of chronic rhinosinusitis in a murine model of sinonasal A. fumigatus infection [80]. Also, mice carrying a loss-of-function mutation in C5 were described to be more susceptible to Aspergillus infections in models of chronic systemic and pulmonary aspergillosis, likely due to defective C5a-dependent recruitment of neutrophils (where effective generation of this anaphylatoxin requires the AP), and, possibly, reduced MAC formation (particularly on germinating conidia and hyphae) [81].…”
Section: The Complement In Animal Models Of Aspergillosismentioning
confidence: 99%
“…Mulligan et al . investigated novel therapeutic targets for chronic rhinosinusitis with nasal polyps (CRSwNP), focusing on complement component C3.…”
Section: Discovery Of Potential Drug Targetsmentioning
confidence: 99%